(3CSGSjGJ GdJShjb (B/s - (3chJdQ, ajdjHs; (3CQeSJQhfL, LGQj s ((3GdQjGV(B: s (3OGQ GdeQjN ddfTQ(B, s, 1998)
(3JYQja GdJShjb hYedjI GdJShjb, age ehbY GdShb hGdeSJgdcjf, JUeje CSJQGJjLjI JShjb bjGOI GdYejd hGdeRjL GdJShjbj, JhSjY GdJShjb, JWhjQ GdfJL GdLOjO, OhQI MjGI GdefJL, GSJQGJjLjI GJUGdGJ GdJShjb GdeJcGedI, GdEYdGf hJQhjL GdeHjYGJ hGdYdGbGJ GdYGeI, GdHjY GdTNUj hGdJShjb GdeHGTQ, GdJShjb aj GdYUQ GdQbej, bjGS GdWdH hGdJfHD Hgs
Keywords: (3GdJShjbs; (3JQhjL GdeHjYGJs